A self-assembled cyclodextrin nanocarrier for photoreactive squaraine - Kauscher, Ulrike; Ravoo, Bart Jan (Beilstein Journal of Organic Chemistry, 2016)
Photoreactive squaraines produce cytotoxic oxygen species under irradiation and have significant potential for photodynamic therapy. Herein we report that squaraines can be immobilized on a self-assembled nanocarrier composed of amphiphilic cyclodextrins to enhance their photochemical activity. To this end, a squaraine was equipped with two adamantane moieties that act as anchors for the cyclodextrin vesicle surface. The supramolecular immobilization was monitored by using fluorescence spectroscopy and microscopy and the photochemistry of the squaraine was investigated by using absorption spectroscopy.
Keywords: cyclodextrin; host–guest chemistry; photodynamic therapy; self-assembly; squaraine